Molecular characterization of a tetraspanin from the human liver fluke, Opisthorchis viverrini. - Supawadee Piratae; Smarn Tesana; Malcolm K Jones; Paul J Brindley; Alex Loukas; Erica Lovas; Veerachai Eursitthichai; Banchob Sripa; Sirikanda Thanasuwan; Thewarach Laha (Public Library of Science (PLoS), 2012)
BACKGROUND: The human liver fluke, Opisthorchis viverrini, is designated as a group 1 carcinogen, and is the major risk factor for cholangiocarcinoma in endemic countries throughout Southeast Asia. Proteins in the excretory-secretory products and tegumental surface membranes of the fluke have been proposed to play pivotal roles in parasite survival in the host, and subsequent pathogenesis. These macromolecules are therefore valid targets for the development of vaccines and new drugs to control the infection. Tetraspanins (TSP) are prominent components of the tegument of blood flukes where they are essential for tegument formation, are directly exposed to the immune system, and are major targets for a schistosomiasis vaccine. We propose that similar molecules in the surface membranes of O. viverrini are integral to tegument biogenesis and will be efficacious vaccine antigens. METHODOLOGY/PRINCIPAL FINDINGS: The cDNA sequence encoding O. viverrini tetraspanin-1 (Ov-TSP-1) was identified and cloned. The Ov-tsp-1gene was isolated from a cDNA library. Ov-tsp-1 mRNA was expressed most highly in metacercariae and eggs, and to a lesser extent in juvenile and adult worms. Immunolocalization with adult flukes confirmed that Ov-TSP-1 was expressed in the tegument and eggs in utero. Western blot analysis of rOv-TSP-1 probed with sera from O. viverrini-infected humans and hamsters indicated that both hosts raise antibody responses against the native TSP. Using RNA interference we silenced the expression level of Ov-tsp-1 mRNA in adult flukes by up to 72% by 10 days after delivery of dsRNA. Ultrastructural morphology of adult worms treated with Ov-tsp-1 dsRNA displayed a distinctly vacuolated and thinner tegument compared with controls. CONCLUSIONS/SIGNIFICANCE: This is the first report of a tetraspanin from the tegument of a liver fluke. Our data imply that tetraspanins play important structural roles in the development of the tegument in the adult fluke. Potential uses of O. viverrini tetraspanins as novel interventions are discussed.